A new model for predicting the decompression behavior of CO2 mixtures in various phases - Gu, S.; Li, Y.; Teng, L.; Hu, Q.; Zhang, D.; Ye, X.; Wang, C.; Wang, J.; Iglauer, Stefan (Elsevier, 2018)
© 2018 Institution of Chemical Engineers The pipeline transportation has been considered as the best way to transport pressurized CO2and plays an important role in Carbon Capture and Storage (CCS) technology. The risk of ductile fracture propagation increases when a CO2pipeline is ruptured or punctured, and CO2decompression behavior must be determined accurately in order to avoid the catastrophic failure of the pipeline and to estimate the proper pipe toughness. Thus in this work, a new decompression model based on GERG-2008 equation of state was developed for modeling the CO2decompression behavior. And for the first time, a relaxation model was implemented to calculate the sound speed in two-phase region. The model predictions were in excellent agreement with experimental ‘shock tube’ test data in the literature. Furthermore, via modeling, it has been demonstrated how impurities in the CO2and initial temperatures would affect the CO2decompression wave speed in various phases. The results obtained show that the effects of these factors on supercritical and gaseous CO2mixtures are absolutely different while liquid CO2mixtures behave very similarly when compared to supercritical CO2mixtures, which indicate that the toughness required to arrest fracture propagation is highly based on the initial phase states of CO2fluid.